(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This document outlines the design and execution of a leg rehabilitation device intended to enhance the recovery of individuals with lower limb disabilities. The device employs principles from biomechanics, engineering, and user-centered design to cater to the varied requirements of patients undergoing rehabilitation due to injuries, surgeries, or neurological disorders affecting the lower extremities. Essential design factors encompass safety, efficacy, usability, adaptability, and alignment with clinical practices. The device features adjustable resistance levels, real-time feedback systems, and customizable rehabilitation programs, allowing for personalized interventions tailored to patients with different abilities and rehabilitation objectives. Clinical validation studies confirm the device’s effectiveness in improving range of motion, muscle strength, balance, and functional mobility, resulting in favorable outcomes for patients. Additionally, usability assessments and clinician feedback underscore the device’s user-friendliness, acceptance, and seamless integration into rehabilitation protocols. Future initiatives will focus on further optimization, technological advancements, and longitudinal studies to assess long-term outcomes and patient satisfaction. In summary, the design and implementation of this leg rehabilitation device present significant potential to improve the quality of care and rehabilitation results for individuals with lower limb disabilities.